Uji Beda Keputusan Sinyal Jual Beli Saham Sebelum dan Sesudah Menggunakan Teknik Moving Average Convergence Divergence (MACD) dan Stochastic Oscillator (SO) - Andrian Dwi Nurcahyo; Eni Dwi Susliyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to partially test whether there are differences in the decision of buy signals and sell signals before and after using the technical analysis of Moving Average Convergence Divergence (MACD) and Stochastic Oscillator (SO) on the LQ45 stock index listed on the Indonesia Stock Exchange (IDX) Banking subsector for the 2018-2022 period. This study used the Wilcoxon Signed Rank Test difference test with a total sample of 4 companies. The research method used is quantitative descriptive comparative type with secondary data. Data selection using purposive sampling and processed using IBM SPSS software version 20.0. The results of this study show that there is a difference in the decision of buy signals and sell signals before and after using MACD technical analysis and there is no difference in the decision of buy signals and sell signals before and after using SO technical analysis. So the implication is that MACD is not accurate, while SO is accurate used in buying signals and selling stock signals. The contribution of the results of this study is empirical evidence that investors do not need to always use MACD and need to always use SO in buying signals and selling stock signals.